On the magnetic ground state of lead-free complex perovskite Sr(Fe1/2Nb1/2)O3 - Kumar A.; Chaudhary A.; Gautam K.; Pandey D. (My University, 2025)
We present here the results of dc magnetization (M) measurements as a function of temperature (T), field (H) and time (t) with different histories and ac susceptibility measurements as a function of temperature and frequency to understand the magnetic ground state of Sr(Fe1/2Nb1/2)O3 (SFN). We show that the zero-field cooled (ZFC) and field cooled (FC) magnetization curves (M(T)) not only bifurcate but also exhibit a short plateau with a dip in the FC M(T) curve suggesting that the observed history dependent irreversibility may be due to cluster spin-glass (CSG) freezing and not superparamagnetic (SPM) blocking. This is confirmed by ac susceptibility χ(ω, T) studies which reveal critical slowing down of the spin dynamics as per Vogel Fulcher and power laws with spin-glass transition temperature TSG ∼(24 ± 1) K. The attempt time obtained by these laws (τ0 ∼10−6 s) is found to be consistent with CSG picture. Further, the field dependent shift of Tf follows de Almeida-Thouless line in the T-H plane with a characteristic critical exponent m = 2/3. Further support for the existence of the spin-glass phase is obtained by the observation of non-exponential decay of the thermoremanent magnetization as well as aging, rejuvenation and memory effects below Tf. The non-zero value of remanent magnetization Mr without saturation below Tf is shown to vanish exponentially with increasing temperature as T → TSG in agreement with what is observed in spin-glass systems. We also present a critical comparison of the magnetic ground states of SFN with CaCu3Ti4O12 (CCTO) and other complex niobate perovskites in terms of the strength of the nearest neighbour exchange interaction parameter J1, the coordination polyhedral, the disorder/dilution level of the magnetic sublattices, the presence or absence of octahedral tilts and the possibility of alternative superexchange pathways in these compounds. © 2020 Elsevier B.V.